1920
DOI: 10.1002/jez.1400300305
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the relative physiological value of spectral lights. II. The sensibility of Volvox to wave‐lengths of equal energy content

Abstract: Estudios sobre el valor fisiol6gico relativo de las luces espectrales.11. La sensibilidad del Volvox a longitudes de onda de igual contenido de energia.La sensibilidad del Volvox a la radiacidn de diferentes longitudes de onda e igual energia (sensibilidad a la radiaci6n de la misma energia) ha sido investigada por 10s autores siguiendo dos mktodos: a) la duraci6n relativa del tiempo de presentacibn, y b) la velocidad relativa de la locomoci6n (y precisi6n de la orientaci6n). Una longitud de onda de 494p tiene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1928
1928
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…In an effort to refute earlier claims that the human PLR was driven exclusively by cones (Brown & Page, 1939), Wagman and Gullberg (1942) examined the spectral sensitivity of the human steady-state PLR for a 0.5 mm criterion response and generated a spectral sensitivity well matched by the scotopic luminosity function and therefore rod dominated. This result is not unreasonable given the small light evoked change in pupil diameter chosen as a criterion response, and it is consistent with the findings of previous and subsequent studies using the same criterion (Alpern & Campbell, 1962, Laurens, 1923). It is interesting to note that, although a 0.5 mm criterion response was chosen by the authors, data throughout the complete range of pupillary diameters was collected and published.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In an effort to refute earlier claims that the human PLR was driven exclusively by cones (Brown & Page, 1939), Wagman and Gullberg (1942) examined the spectral sensitivity of the human steady-state PLR for a 0.5 mm criterion response and generated a spectral sensitivity well matched by the scotopic luminosity function and therefore rod dominated. This result is not unreasonable given the small light evoked change in pupil diameter chosen as a criterion response, and it is consistent with the findings of previous and subsequent studies using the same criterion (Alpern & Campbell, 1962, Laurens, 1923). It is interesting to note that, although a 0.5 mm criterion response was chosen by the authors, data throughout the complete range of pupillary diameters was collected and published.…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that the pupils of rod achromats continues to respond to light increments well over levels commonly accepted to saturate rod photoreceptors (Alpern, Falls & Lee, 1960), thus implying that an additional photopigment is involved in the pupillary responses of these individuals. Additionally, spectral sensitivity measurements of pupillary constriction to steady state illumination have shown short wavelength sensitivity that is not well matched by either rod or S-cone contributions (Bouma, 1962, Laurens, 1923). Historical investigations of the response dynamics of the PLR are also suggestive of a role for ipRGCs in the behavior of the pupil in response to light increments.…”
Section: Introductionmentioning
confidence: 99%
“…Since the spectral sensitivities of the photopic and scotopic eye are well established the identification of the photoreceptors activating the pupil should be readily achieved by measuring the spectral characteristics of the response of the pupil to retinal stimulation. Laurens (1923) was able to demonstrate that the curve relating pupil size to wave-length (equal energy spectrum) depended upon the adaptation state of the eye. The curve for the light-adapted eye had a minimum at 554-2 m,u, the dark-adapted curve had one at 514-3 m,u.…”
mentioning
confidence: 97%
“…I t has been considered either as consisting of a series of phobic reactions (11,17,39,46,57) and therefore termed "pseudo-topotaxis" (39,46), in which the orientation is postulated to be dependent on a periodic shading of the photoreceptor (11,17,39,46), or as a mechanism totally dif ferent from phobotaxis (4,11,35,45). Later the maximum in the blue-green light has been repeatedly verified for unicellular and colonial forms of flagellates (44,45,48). Conclusions as to the nature of the pigments active in phototaxis are based almost exclusively on investigations of the spectral sensitivity of the algae.…”
Section: Phototaxis Of Flagellatesmentioning
confidence: 99%